Perspektif kepuasan mahasiswa : Pengaruh good university governance terhadap kompetensi tenaga pengajar dan fasilitas pendidikan - Sari, Yetri Martika (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to examine the effect of good university governance and its indicators on indicators of competence of lecturer and learning facilities in terms of student satisfaction perspective. The research data was collected using a questionnaire and obtained 278 respondents who are active students at Strata 1 level at the State Islamic Religious College in Bandar Lampung. This research is a quantitative research and uses smartPLS in processing data. The results of this study confirm the notion that good university governance has an effect on student satisfaction on the competence of lecturer and learning facilities, partially supported. This study provides insight that not all indicators of good university governance have an influence on indicators of student satisfaction on the competence of lecturer and learning facilities. This result can be used as a reference in managing higher education institutions to achieve the mission of a world class university and the implementation of an independent campus policy.